Terrorism revisited : Islamism, political violence and state-sponsorship - Casaca, Paulo ; Wolf, Siegfried O. (Springer, 2020)
Contents: Preface; Redefining Terrorism; Contents; About the Editors; Part I: Reassessing Terrorism; The Conceptual Discussion on Terrorism; 1 Terrorism, What Terrorism?; 2 Terrorism, Crime and Other Sorts of Violence; 3 The Psychology of the Bomb; 4 Terrorism: The Pure One or the One that Matters?; 5 Does Terrorism Necessarily Target Civilians?; 6 The Semantics of Terrorism; 7 Countless Shades of Horror; 8 Appease the Devil and Shoot the Innocent?; 9 Terrorism Revisited; References; New Terrorism; 1 The Perception of ̀̀New Terrorism;́́ 2 The Transcendental Perspective. Contents: 3 Perspectives on Suicide Terrorism4 New Terrorism or New World?; 5 The Drawbacks of the Framework of Counterterrorism; References; Part II: Case Studies; The Evolution and Ascension of Iranś Terror Apparatus; 1 Introduction; 2 Fadaíyan-e Islam: Devotees of Islam; 3 Khomeini During the Pre-Revolution Era; 4 Guardians of the Islamic Revolution; 5 Khomeiniś Culture of Martyrdom-Seeking Ushered Terrorism into a New Era; 6 Khomeiniś Islamic Republic Is the Leading State Sponsor of Terrorism; 7 The Iran-Al-Qaeda Connection; 8 Conclusion; References. Contents: 3 The ̀Unholy Triangular Nexus:́ Islamization and the Principal-Agent Relations Between Military and Terrorists4 The Concept of State-Sponsored Terrorism; 4.1 Indicators for State Terrorism; 4.2 Forms of State Terrorism; 5 Pakistan and State-Sponsored Terrorism; 5.1 Case Study 1: East Pakistan (Bangladesh); 5.1.1 The Context and Initial Conditions; 5.1.2 Indicators; Intentional Target Killings of Civilians; Systematically Organized; Political Motive; On Behalf of or in Conjunction with the State; Secrecy; Ethnic Cleansing by the State. Contents: Build-Up and Support Sponsorship of Non-state Terrorist Groups (Death Squads)Massacres and Genocide; Extraordinary Brutality and Spreading Fear; 5.2 Case Study 2: Afghanistan; 5.2.1 The Context and Initial Conditions; 5.2.2 Indicators of State-Sponsored Terrorism; On Behalf of or in Conjunction with the State; Creating and Using Fear; Political Motives; Secrecy; Systematically; Extraordinary Brutality; Intentional Targeting of Civilians; Diplomacy and Protection for Terror Groups; 5.3 Case Study 3: India; 5.3.1 The Context and Initial Conditions; Jammu and Kashmir (JandK). Contents: Evolution and Rise of Contemporary Jihadism: From the Muslim Brotherhood to IS1 Introduction; 2 Jihad: From Anti-Imperialism to Anti-Semitism; 3 After Al-Banna: The Development of Takfir; 4 The Islamic Revival; 5 The Causes and Legacy of the Great Mosque Siege; 6 Afghanistan and the Afghan Arabs; 7 The Gulf War and the Jihad Against America; 8 The Destruction of Iraq and the Rise of Zarqawi; 9 The Betrayal of the Sunni Awakening; 10 Conclusion; References; Pakistan and State-Sponsored Terrorism in South Asia; 1 Introduction; 2 A Praetorian State: The Role of the Military in Pakistan Politics.